Medical "Gatekeeping" for Psychosocial Research on Serious Illness: Bioethical Reflections. (July 2020) - McGrath, Pam; Kaur, Amandeep; Feracho, Rennette; Patton, Mary Anne
The discussion explores ethical issues associated with medical "gatekeeping" in relation to psychosocial health research associated with serious illness and loss. "Gatekeeping" is defined as the process whereby health-care providers prevent access to eligible patients for research recruitment. The impact of this practice on the research process is explored, including issues of sample representation, selection bias, and wastage of time and resources. The reflection of ethical issues is set in the context of research on clinical empathic responsiveness and accuracy, paternalism, and the ethical principles of autonomy, beneficence, and justice.